Gorham-Stout disease involving ipsilateral clavicle and scapula in a child – a case report focusing on imaging and histopathological features of this extremely rare condition - Duczkowski, Marek; Palczewski, Piotr; Wagrodzki, Michał; Duczkowska, Agnieszka; Klepacka, Teresa; Szymborska, Agnieszka; Raciborska, Anna; Czubak, Jaroslaw; Bekiesinska-Figatowska, Monika (Polish Journal of Pathology, 2021)
Gorham-Stout disease (GSD) is a very rare entity of unknown etiology, characterized by excessive intra-osseous proliferation of blood or lymphatic vessels, resulting in progressive resorption of bone matrix and destruction of bone. To date we have found only seven published cases concerning fully confirmed GSD of the shoulder girdle bones in children. Our case concerns an 8-year-old boy with involvement of the left clavicle and scapula. The knowledge of imaging and histopathological features is crucial for establishing the diagnosis of GSD, therefore the exchange of experiences in this field is essential for improving the care of affected patients.